Health and wellbeing in the Arctic : the critical issues of food insecurity and suicide among indigenous people - Sveinbjörg Smáradóttir 1985- (2018)
Frumbyggjar Norðurslóða eru almennt við verri heilsu en aðrir íbúar svæðisins. Síðan afkomendur Evrópubúa hófu að leggja undir sig heimalönd frumbyggjanna, og fram á síðari hluta 20. aldar, gengu þeir í gegnum átakamiklar félagslegar- og efnahagslegar umbyltingar, voru neyddir til að yfirgefa heimalönd sín, samlagast og „nútímavæðast“ vestrænni menningu með alvarlegum afleiðingum fyrir heilsu þeirra og velferð. Í þessari ritgerð er fjallað um tvo mikilvæga þætti er varða heilsu og velferð frumbyggja á Norðurslóðum. Annarsvegar er það fæðu-óöryggi, orsakir og afleiðingar, og sambandið milli hefðbundinnar fæðu og leiða til fæðuöflunar og „vestræns“ mataræðis. Hinsvegar er fjallað andlega heilsu frumbyggjanna, með sérstaka áherslu á sjálfsvíg, orsakir og afleiðingar, hvernig þau tengjast atburðum og áföllum fortíðar og er viðhaldið af áskorunum sem frumbyggjarnir standa frammi fyrir í dag. Across the Arctic region, indigenous people fare worse on almost every health indicator than their non-indigenous counterparts. Since the time when the Arctic became colonized by non-indigenous people and until the late 20th century, the indigenous people have gone through rapid and dramatic socioeconomic changes, including forced relocation and modernization, and have endured assimilation strategies at the hands of the dominant cultures with often detrimental effects on their health and wellbeing. In this thesis, two fundamental issues regarding the health and well-being of indigenous people in the Arctic will be discussed. On the one hand, I examine food insecurity, its causes and consequences, and the relationship between the traditional and non-traditional food sector. On the other hand, I discuss the mental health of Arctic indigenous people, with particular emphasis on high prevalence of suicide and how it is derived from past and present trauma and maintained by social, economic and environmental factors and conditions.